Adherence to Mediterranean diet and 10‐year incidence (2002–2012) of diabetes: correlations with inflammatory and oxidative stress biomarkers in the ATTICA cohort study. Issue 1 (27th July 2015) - Koloverou, E.; Panagiotakos, D. B.; Pitsavos, C.; Chrysohoou, C.; Georgousopoulou, E. N.; Grekas, A.; Christou, A.; Chatzigeorgiou, M.; Skoumas, I.; Tousoulis, D.; Stefanadis, C.
Abstract: Background: The purpose of this work was to investigate the links between oxidative stress, inflammation and coagulation and their effect on Mediterranean diet–diabetes relationship. Methods: In 2001–2002, a random sample of 1514 men (18–87 years old) and 1528 women (18–89 years old) was selected to participate in the ATTICA study, where Athens is the major metropolis. A validated questionnaire was used to assess lifestyle and dietary factors. Adherence to Mediterranean diet was recorded using MedDietScore . Among others, oxidative stress and inflammatory biomarkers were recorded. During 2011–2012, the 10‐year follow‐up was performed. Diabetes incidence was defined according to the American Diabetes Association criteria. Results: A total of 191 incident cases of diabetes were documented, yielding an incidence of 12.9% (13.4% in men and 12.4% in women). Medium and high adherence was found to decrease diabetes risk by 49% (95% CI: 0.30, 0.88) and 62% (95% CI: 0.16, 0.88), respectively, compared with low adherence. A logarithmic trend between Mediterranean diet and diabetes incidence was also revealed ( p for trend = 0.042). Individuals with abnormal waist circumference (>94 for men, >80 for women) were benefited the most. Wholegrain cereals, fruits and legumes had the greatest predictive ability. The anti‐diabetic effect of Mediterranean diet correlated with measurements of tumour necrosis factor‐ α, homocysteine and total antioxidant capacity. Conclusions: The reported results support the role of Mediterranean diet as a promising dietary tool for the primary prevention of diabetes, by attenuating inflammation and fostering total antioxidant capacity. This dietary pattern may have therapeutic potential for many cardiometabolic disorders associated with inflammation and/or oxidative stress. Copyright © 2015 John Wiley & Sons, Ltd.